Myocarditis as the first manifestation of eosinophilic granulomatosis with polyangiitis - Djordjević Radojković, Danijela; Apostolović, Svetlana; Damjanović, Miodrag; Kostić, Tomislav; Fejsa Levakov, Aleksandra; Dimitrijević, Marko; Janković Tomašević, Ružica; Dakić, Sonja; Božinović, Nenad; Pavićević, Milena (Vojnosanitetski pregled, 2023)
Introduction. Myocarditis is not a rare diagnosis, but its etiology often remains unknown as it requires extensive diagnostic work. Eosinophilic granulomatosis with polyangiitis (EGPA) or Churg-Strauss syndrome is a very rare systemic disease that is not easy to diagnose. Myocarditis in EGPA is uncommon and usually occurs in the late stages of the disease. Case report. A 22-year-old man was admitted with acute coronary syndrome. Using coronary angiography, the presence of stenoses on the epicardial coronary arteries was ruled out, and a working diagnosis of myocardial infarction with non-obstructive coronary arteries (MINOCA) was established. Then, we found inflammatory syndrome, eosinophilia, and a lot of systemic symptoms and signs. The diagnostic work included extensive laboratory tests, which ruled out infectious agents. Then, immunological tests, a computed tomography scan of the chest, cardiac magnetic resonance imaging (MRI) and a biopsy of the bone marrow, nasal mucosa, and skin were performed. We managed to establish the diagnosis of myopericarditis by cardiac MRI. The cause of myocarditis – EGPA, was found only after the histopathological finding of the skin biopsy, which enabled adequate immunosuppressive therapy. Conclusion. The accurate diagnosis was crucial for the correct, causal treatment of the patient, especially because he needed life-long immunosuppressive therapy. In order for such complex patients to receive adequate treatment, a multidisciplinary approach and perseverance in the diagnostic evaluation of the etiology of myocarditis are necessary.
Keywords: diagnosis; histological techniques; myocarditis; eosinophilia; churg-strauss syndrome